Can Education Reduce Political Polarization? Fostering Open-Minded Political Engagement during the Legislative Semester. Issue 5 (May 2019) - Levy, Brett; Babb-Guerra, Annaly; Batt, Lena M.; Owczarek, Wolf
Background: In the United States, elected leaders and the general public have become more politically polarized during the past several decades, making bipartisan compromise difficult. Political scientists and educational scholars have argued that generating productive political cooperation requires preparing members of democratic societies to productively negotiate their political disagreements. Numerous prior studies on civic learning have focused on fostering youth political engagement, but little research has examined how educators can support both political engagement and political open-mindedness. Purpose: The study described in this paper explores how students' experiences in a unique high school government course may help to foster their open-minded political engagement (OMPE), which we define as an individual's propensity to explore and participate in political affairs while maintaining a willingness to adjust one's political views. Research Design: Using quantitative and qualitative methods, we examined the development of adolescents' OMPE during their participation in high school government courses at three schools. Whereas participants at Standard High (N = 87) completed a traditional government course, students at Green High (N = 224) and Gomez High (N = 94) were enrolled in the Legislative Semester course, an extended political simulation that required students to research, discuss, debate, and mock-vote on controversial public issues. At each research site, we gathered data during the fall 2014–15 semester through student surveys, teacher and student interviews, and classroom observations. We analyzed survey data using principal component analysis, t tests, and OLS regression, and we conducted constant comparative analysis with our qualitative data. Findings: Students in the LS program became more politically engaged and open-minded than students in the traditional government course. Whereas studying and exploring various political issues was especially helpful for the development of political engagement, considering diverse political perspectives in an open classroom environment was helpful for the development of political open-mindedness. However, if students in the LS were encouraged to be partisan, they were less likely to develop greater political open-mindedness. Conclusions: Repeated opportunities to examine diverse political ideas with peers can foster the development of open-minded political engagement. Educators can support such exchanges not only by structuring substantive sharing of diverse political perspectives, but also by creating emotionally "safe" classroom environments, encouraging the expression of minority viewpoints, and de-emphasizing partisan uniformity. Encouraging careful listening—rather than polite hearing—may be central for the development of political open-mindedness. For too many of us, it's become safer to retreat into our own bubbles … surrounded by people who look like us and share the same political outlook and never challenge our assumptions…. Without a willingness to admit new information and concede that your opponent is making a fair point, and that science and reason matter, we'll keep talking past each other, making common ground and compromise impossible.—Barack Obama, "Farewell Address" (2017)